THE EFFECT OF FLIPPED CLASSROOM TEACHING MODEL TO THE WRITING ABILITY OF EIGHTH GRADE STUDENTS AT SMP SWASTA DR. CIPTO MANGUNKUSUMO BANDAR JAWA ON A RECOUNT TEXT - Basar Lolo Siahaan; Yevana Arthika Hutagaol; Mungkap Mangapul Siahaan (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
The researcher decided to implement the Flipped Classroom in this research. The aim of this research is to determine the effect of using the Flipped Classroom on the writing of recount text for eighth grade students at SMP Swasta Dr. Cipto Mangunkusumo Bandar Jawa in the 2024/2025 academic year. This research used a quasi-experimental design with quantitative methods. In this research, researchers used two classes, namely the experimental class and the control class. Researchers took a class VIII population of 85 students. For the sample, in the experimental class and control class the number of students was the same, namely 30 people. The sample of students in class VIII-1 and control class VIII-2 was selected using purposive sampling technique. And to analyze the data, researchers used the t-test formula to find out whether using Flipped Classroom has an influence on students' writing of recount text . After data analysis, the research results showed the average pre-test and post-test scores in the experimental class and the average pre-test and post-test scores in the control class. In the experimental class the average pre-test score was 59.5 and post-test was 78.3. And in the control class the average pre-test score was 59.53 and the post-test was 68. The standard deviation in the experimental class was 1,224.5 and the standard deviation in the control class was 1,627. After calculating the mean and standard deviation for both classes, the researcher calculates using the t test formula, the t test result must be the highest value from the t table with a significance level of 5% (3.345 > 1.672).